Roses or Lemons: Adverse Selection in the Market for Thoroughbred Yearlings - Chezum, Brian; Wimmer, Brad (The Review of Economics and Statistics, 1997)
This paper tests for the presence of adverse selection in thoroughbred yearling auction markets. Thoroughbred auctions consist of two seller types: sellers who breed horses to race and sell (racers) and sellers who take all their yearlings to auction (breeders). If racers use private information, keeping those yearlings with a higher probability of on-track success, they are likely to receive a lower price for similar yearlings as compared to breeders. Using data from Keeneland's 1994 September yearling sale, we find support for this hypothesis. We improve on previous studies by analyzing the distinction between seller types on a continuous scale.